Obserwatora i uczestnika spojrzenia na wojnę albo o obojętności i zaangażowaniu - Roman Kwiecień (Ksiegarnia Akademicka Publishing, 2018)
Observer’s and Participant’s Views on War or about Indifference and Commitment. Deliberations under Kant’s Philosophy The article seeks to draw attention to Kant’s look at war and its importance for today’s debate on the use of force. Kant’s views on war are usually considered equivalent with his standpoint presented in Zum ewigen Frieden. However, Kant’s political philosophy offers broader perspective of the war problem. This perspective takes into account two standpoints, namely, the non‑involved observer standpoint and the committed participant one. The former tries to explain the war phenomenon, whereas the latter assesses it. Surprisingly enough, war can make to Kant a measure of progress within human society and leads to a real civitas gentium, that is, to society without wars which embodied the ideal of ‘perpetual peace’. According to Kant, such progress must be grounded on ‘revolution of freedom’ because individual human freedom conditions both moral maturity of mankind and political freedom. Unfortunately, taking into account a practise of domestic and international relations Kant turned out to be an excessive optimist.